Effect Of Some Antimicrobial Agents On Direct Shoot Organogenesis In Oxalis Corniculata (L.) (Applied Biological Research, 2023)
The present study focused on the effect of antimicrobial agents on direct shoot  organogenesis in Oxalis corniculata Linn. The antimicrobial agents evaluated  were kanamycin, carbendazim, cefotaxime and silver thiosulphate. The nodal  explants, collected from 4-week old shoots of field grown O. corniculata plants, were sterilized by 5% (v/v) Tween-20, followed by 70% ethanol. MS  medium was supplemented with alone or in combinations of benzyl aminopurine(BAP), kinetin, naphthalene acetic acid (NAA), indole-3-butyric acid and indole 3-acetic acid. Among the antimicrobial agents tested, carbendazim @ 2 mg L-1 along with BAP @ 1 mg L-1 gave maximum shooting response (80%), higher  shoot number (7.8) and longer shoots (4.7 cm); whereas kanamycin (40 µM)  showed least response on shooting (75%) and shoot number (4.5). Among the  auxins tested, NAA @ 2 mg L-1showed maximum rooting response (95%), root number (22.3) and root length (4.4 cm). Rooted shootlets were successfully  hardened in sterile soil + vermiculite (1:1) medium and then transferred to the  field. Among the antimicrobial agents tested, carbendazim + BAP resulted in  best response on shooting while NAA showed maximum rooting response.
Keywords: Antimicrobial agents; carbendazim; silver thiosulphate; direct organogenesis; Oxalis corniculata